2021
DOI: 10.1186/s12879-021-06027-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hookworm infection and anthelmintic treatment on naturally acquired antibody responses against the GMZ2 malaria vaccine candidate and constituent antigens

Abstract: Background Malaria and helminths diseases are co-endemic in most parts of sub-Saharan Africa. Immune responses from each of these pathogens interact, and these interactions may have implications on vaccines. The GMZ2 malaria vaccine candidate is a fusion protein of Plasmodium falciparum merozoite surface protein 3 (MSP3) and glutamate rich protein (GLURP R0). GMZ2 has recently showed modest efficacy in a phase IIb multicenter trial. Here, we assessed the effect of hookworm (Necator americanus) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 33 publications
0
19
2
Order By: Relevance
“…This hypothesis, however, is not supported by data of increase in P. falciparumspecific IgG1 and IgG3 during coinfection with S. haematobium (Diallo et al, 2010). Similarly, P. falciparum coinfection with hookworm increased IgG1 and IgG3 levels to the GMZ2 vaccine and related antigens, while deworming treatment reduced these IgG1 and IgG3 levels (Amoani et al, 2021). On the other hand, following the synergy hypothesis, our results could be beneficial for helminth immunity assuming that IgE has a protective effect.…”
Section: Discussioncontrasting
confidence: 80%
“…This hypothesis, however, is not supported by data of increase in P. falciparumspecific IgG1 and IgG3 during coinfection with S. haematobium (Diallo et al, 2010). Similarly, P. falciparum coinfection with hookworm increased IgG1 and IgG3 levels to the GMZ2 vaccine and related antigens, while deworming treatment reduced these IgG1 and IgG3 levels (Amoani et al, 2021). On the other hand, following the synergy hypothesis, our results could be beneficial for helminth immunity assuming that IgE has a protective effect.…”
Section: Discussioncontrasting
confidence: 80%
“…In the case of P. falciparum , the synergy hypothesis is supported by an increase in P. falciparum -specific IgG1 and IgG3 during coinfection with S. haematobium ( 40 ). Similarly, P. falciparum coinfection with hookworm increased IgG1 and IgG3 levels to the GMZ2 vaccine and related antigens, while deworming treatment reduced these IgG1 and IgG3 levels ( 48 ). Second, our observation of higher magnitude and breadth of response to P. falciparum and helminth antigens in coexposed/coinfected individuals could be explained by the ability of P. falciparum and helminths to induce polyclonal B cell responses ( 49 , 50 ), which is particularly evident for IgE during helminth infections ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…In line with this result, when analyzed individually, IgM and IgG1 anti-MSP3 levels decreased after deworming. The study did not identify a significant association between coinfections and the increase in specific antibodies to MSP3 in an individual manner 44 .…”
Section: Msp3-glurp (Gmz2)mentioning
confidence: 62%
“…Amoani et al . 44 observed the influence of hookworm disease ( Necator americanus ) and antithelmintic treatment on the response of naturally acquired anti-GMZ2 antibodies and constituent antigens. It was reported that individuals who had coinfections with Plasmodium falciparum and hookworm had a significant increase in IgG3 levels against GMZ, compared with the group infected only with P. falciparum and the control group.…”
Section: Msp3-glurp (Gmz2)mentioning
confidence: 99%